1990
DOI: 10.1111/j.1471-6402.1990.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Number and Quality of Roles: A Longitudinal Personality View

Abstract: We used longitudinal personality data to test whether number and quality of roles were associated with health and self‐enhancement in 100 privileged midlife women. Number of roles (from the set of partner, parent, and worker) was not related to autonomy, individuality, and complexity, as had been hypothesized, but to respect for norms, being well‐organized considering oneselt like other people. Through women with one role were lower in well‐being than women with more than one, hierarchical multiple regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 21 publications
2
24
0
2
Order By: Relevance
“…Results of this study emphasize the need to examine the quality as well as the quantity of roles when determining psychological well-being of midlife women (Baruch & Barnett, 1986). Another study supported this conclusion by showing that, after age 21, increasing the number of roles women held did not have significant effects on wellbeing, but the quality of those roles, as assessed by marital satisfaction and status level achieved in the workforce, was associated with contentment and effective functioning (Helson, Elliot, & Leigh, 1990). Thus, it seems that wellbeing can be predicted only by considering the multiple factors that influence a woman's experience of her roles.…”
Section: Roles Of Women At Midlifementioning
confidence: 61%
“…Results of this study emphasize the need to examine the quality as well as the quantity of roles when determining psychological well-being of midlife women (Baruch & Barnett, 1986). Another study supported this conclusion by showing that, after age 21, increasing the number of roles women held did not have significant effects on wellbeing, but the quality of those roles, as assessed by marital satisfaction and status level achieved in the workforce, was associated with contentment and effective functioning (Helson, Elliot, & Leigh, 1990). Thus, it seems that wellbeing can be predicted only by considering the multiple factors that influence a woman's experience of her roles.…”
Section: Roles Of Women At Midlifementioning
confidence: 61%
“…While the findings in this area are not definitive, much of the recent research has reported beneficial psychological and physical health effects of paid work for women, particularly if they are satisfied with the work (see e.g. Bullers, 1994;Crosby, 1987;Helson, Elliot, & Leigh, 1990;Rodin & Ickovics, 1990;Smith, Shelley, & Dennerstein, 1994).…”
Section: The Strong and Positive Associationmentioning
confidence: 95%
“…A large body of research indicates that the quality of women's social role involvements has important consequences for their well-being in midlife (Barnett & Baruch, 1985;Baruch & Barnett, 1986;Baruch, Biener & Barnett, 1987;Crosby, 1987;Gerson, 1985;Helson, Elliot, & Leigh, 1990;Reifman, Biernat, & Lange, 1991;Vandewater, Ostrove, & Stewart, 1997). Based upon this literature, we now know that the quality of experiences in roles, rather than the sheer number of role involvements, is more influential for women's well-being in midlife.…”
Section: Introductionmentioning
confidence: 91%